2021
DOI: 10.3390/toxics9110291
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Bisphenols Concentration with Asthma in Korean Adolescents: Data from the Third Korean National Environmental Health Survey

Abstract: The effects of bisphenol A (BPA) on asthma have been reported in various in vitro, animal, and human epidemiologic studies. However, epidemiological studies on the effects of bisphenol S (BPS) and bisphenol F (BPF), which are substitutes of BPA, on asthma are lacking. The purpose of this study was to identify the association between BPA, BPS, and BPF and asthma. An asthma-related questionnaire; urinary BPA, BPS, BPF; and the possible confounders were analyzed among 922 adolescents aged 12–17 years who particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The levels of bisphenol S and F, analogs of bisphenol A, widely used in plastic products, were higher in urine collected from females diagnosed with asthma as compared to healthy controls. At the same time, no differences were observed in males 13 . We are curious and ready to learn more.…”
Section: Figurementioning
confidence: 90%
“…The levels of bisphenol S and F, analogs of bisphenol A, widely used in plastic products, were higher in urine collected from females diagnosed with asthma as compared to healthy controls. At the same time, no differences were observed in males 13 . We are curious and ready to learn more.…”
Section: Figurementioning
confidence: 90%
“…However, urinary triclosan and propyl and butyl parabens but not BPA levels were associated with IgE to foods or inhalants in children (117). Bisphenol S does not safely replace BPA (118)(119)(120). Further studies are warranted to determine the effects of BPA on the immune system in infants.…”
Section: Bisphenol Amentioning
confidence: 99%
“…In fact, the negative effects of BPS may be stronger than those of BPA ( 39 ). Although most studies have confirmed the health hazards of BPF and BPS ( 40 43 ), stringent regulations are yet to be implemented in multiple countries, including Taiwan.…”
Section: Introductionmentioning
confidence: 99%